Knowledge, attitudes, and behaviors of dentists regarding child physical abuse in Jeddah, Saudi Arabia. (April 2016) - Mogaddam, Meaad; Kamal, Iman; Merdad, Leena; Alamoudi, Najlaa
Abstract: A large proportion of child physical abuse cases go undocumented and unreported. Dentists can play an important role in identifying and reporting these cases, but little has been reported about this issue in Saudi Arabia. The aims of the study were to (1) assess dentists' knowledge of child physical abuse, (2) assess dentists' attitudes towards child physical abuse, and (3) assess the behaviors of dentists in identifying and reporting child physical abuse. A cross-sectional survey of pediatric dentists, pediatric dentistry residents, and dental interns practicing at all of the dental schools in Jeddah, Saudi Arabia was conducted using an anonymous, self-administered questionnaire. The participants in current study demonstrated insufficient knowledge of the signs and symptoms of child physical abuse, actions that should be taken in suspected cases, circumstances in which to report such cases, and the legal authorities to which they should be reported. The attitudes of participants towards detecting and reporting cases were generally positive. Only 11% of the participants had suspected a case of child abuse, and only 3% of them reported it. Lack of knowledge about referral procedures and fear of anger from family members were the main causes of underreporting. In conclusion, this study showed that dentists have insufficient knowledge about child physical abuse but positive attitudes towards their role in detecting and reporting it. This topic should be covered and emphasized in dental schools' curricula, and healthcare and academic institutes must have a clear protocol to be followed if a case of abuse is suspected.